Mixed epithelial and stromal tumour of the kidney masquerading as hydatid cyst: a rare case report from the developing world - Mahar, Naveed Ahmed; Mushtaq Hussain; Shah, Syed Arslan Shehzad; Qureshi, Harris Hassan; Kalwar, Sara Rasheed; Sultan, Gauhar (Journal of the Pakistan Medical Association, 2023)
Mixed epithelial and stromal tumour (MEST) is a rare entity with an incidence of 0.2% among renal cancers. It has strong predilection towards females with a 1:6 male to female ratio, the tumour is cystic with some solid component with biphasic proliferation of stromal and epithelial cells. The case of a 37-years-old female is presented with right lumbar pain since 3 months. The family history was unremarkable. The routine workup revealed mild neutrophilia and borderline Echinococcus antibody titres. Ultrasound revealed a complex cystic lesion with a solid component in the right kidney. CT scan with contrast confirmed a multiloculated mixed density lesion with daughter cysts arising from the middle lobe of the right kidney. Initial diagnosis of renal hydatid cyst was established and she underwent partial nephrectomy with excision of the cystic mass. Surprisingly the histopathology revealed mixed epithelial and stromal tumour.